Electronic theodolite intersection systems - Bingley, R.M. (1990)
The development of electronic surveying instruments, such as electronic theodolites, and concurrent advances in computer technology, has revolutionised engineering surveying; one of the more recent examples being the introduction of Electronic Theodolite Intersection Systems (ETISs).